2022
DOI: 10.1002/aur.2802
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing in 16p11.2 deletion and 16p11.2 duplication

Abstract: Deletions and duplications at the chromosomal region of 16p11.2 have a broad range of phenotypic effects including increased likelihood of intellectual disability, autism, attention deficit hyperactivity disorder (ADHD), epilepsy, and language and motor delays. However, whether and how sensory processing is affected has not yet been considered in detail. Parents/caregivers of 38 children with a 16p11.2 deletion and 31 children with a 16p11.2 duplication completed the Sensory Behavior Questionnaire (SBQ) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…Importantly, our results could not be explained by differences in motor latencies or perceptual decision criteria between the groups. Together, the current results add to a growing body of literature demonstrating differences in sensory processing in 16p11.2 deletion (Smith et al, 2022), and suggest that visual functions like binocular rivalry may help to characterize putative alterations in sensory functions in autism genetic subgroups.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Importantly, our results could not be explained by differences in motor latencies or perceptual decision criteria between the groups. Together, the current results add to a growing body of literature demonstrating differences in sensory processing in 16p11.2 deletion (Smith et al, 2022), and suggest that visual functions like binocular rivalry may help to characterize putative alterations in sensory functions in autism genetic subgroups.…”
Section: Discussionsupporting
confidence: 73%
“…Although 16p11.2 deletions are well-documented genetic alterations associated with autism, only a few studies have focused on phenotypically characterizing these two conditions, especially in the sensory domain. One recent questionnaire-based study reported high levels of parent-reported sensory processing difficulties in individuals with 16p, at similar levels as is commonly reported for individuals with autism (Smith et al, 2022), highlighting the important of empirically studying sensory processes in the condition. Along these lines, one study demonstrated reductions in selective visual attention using a video game paradigm in children with 16p11.2 deletion (Anguera et al, 2016), and an eye-tracking study demonstrated a relative reduction in top-down as compared with bottom-up attention to images of real world scenes for individuals with 16p11.2 (Haskins et al, 2022).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The disruption of correlated activity in neural networks located in discrete brain areas could give rise to a range of behavioral symptoms exhibited by individuals with NPDs, by disrupting the sparse coding patterns, increasing noise or impairing the processing of salient signals 61 64 . For example, excessive synchrony in local somatosensory and visual cortices could provoke enhanced sensory sensitivity exhibited by 16p11.2 duplication carriers 65 . Alternatively, aberrant synchrony may contribute to ‘noisy networks’ which impair information processing and undermine higher-order cortical processing 66 68 .…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of correlated activity in neural networks located in discrete brain areas could give rise to a range of behavioral symptoms exhibited by individuals with NPDs, by disrupting the sparse coding patterns, increasing noise or impairing the processing of salient signals 61,62,63,64 . For example, excessive synchrony in local somatosensory and visual cortices could provoke enhanced sensory sensitivity exhibited by 16p11.2 duplication carriers 65 . Alternatively, aberrant synchrony may contribute to 'noisy networks' which impair information processing and undermine higher-order cortical processing 66,67,68 .…”
Section: Implications Of Circuit Phenotypes For Other Npdsmentioning
confidence: 99%